2021
DOI: 10.2147/ott.s291812
|View full text |Cite
|
Sign up to set email alerts
|

Increased HSF1 Promotes Infiltration and Metastasis in Cervical Cancer via Enhancing MTDH-VEGF-C Expression

Abstract: Purpose To explore the molecular mechanism of promoting cervical cancer by HSF1 in vivo and in vitro. Methods The expression of HSF1 in 110 paraffin-embedded cervical cancer sections of different grades was examined via immunohistochemistry analyses. Expression of HSF1 downstream targets Metadherin (MTDH), VEGF-C and CD31 were studied using immunohistochemistry analyses. HSF1 transcriptional activity in the MTDH promoter region was detected by EMSA, CHIP and luciferase.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Past studies have shown that HSF1 reduced macrophage infiltration by inhibiting the transcription of monocyte chemoattractant protein‐1 (MCP‐1)/chemokine (C‐C motif) receptor 2 (CCR2) and attenuated LPS‐induced acute liver injury in mice 37 . In addition, HSF1 promoted the proliferation, metastasis and invasion of cervical cancer by promoting the expression of MTDH via binding to the MTDH promoter 38 . In sepsis, HSF1 exerted a protective role against multiple organ dysfunction in sepsis by inhibiting coagulation activity and microthrombosis through direct upregulation of t‐PA 17 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Past studies have shown that HSF1 reduced macrophage infiltration by inhibiting the transcription of monocyte chemoattractant protein‐1 (MCP‐1)/chemokine (C‐C motif) receptor 2 (CCR2) and attenuated LPS‐induced acute liver injury in mice 37 . In addition, HSF1 promoted the proliferation, metastasis and invasion of cervical cancer by promoting the expression of MTDH via binding to the MTDH promoter 38 . In sepsis, HSF1 exerted a protective role against multiple organ dysfunction in sepsis by inhibiting coagulation activity and microthrombosis through direct upregulation of t‐PA 17 .…”
Section: Discussionmentioning
confidence: 99%
“…37 In addition, HSF1 promoted the proliferation, metastasis and invasion of cervical cancer by promoting the expression of MTDH via binding to the MTDH promoter. 38 In sepsis, HSF1 exerted a protective role against multiple organ dysfunction in sepsis by inhibiting coagulation activity and microthrombosis through direct upregulation of t-PA. 17 Interestingly, we found that GA ameliorated microthrombosis and coagulopathy in septic mice via the pathways described above, thereby ameliorating multiple organ dysfunction. This effect may be achieved by increasing the stability of the active HSF1 trimer.…”
Section: Discussionmentioning
confidence: 99%
“…3A-B). HSF1 has previously been associated with outcomes for many cancer types and the HAS reflected many of these known associations including liver (55,56), lung (57), pancreatic (58), melanoma (46), esophageal (48), cervical (59), and head/neck (60) cancers (Fig. 3A-B).…”
Section: Resultsmentioning
confidence: 88%
“…Currently, only HSF1 has been reported in sepsis-related studies. HSF1 activation is regulated by a multimolecular chaperone complex composed of HSP40, HSP70, and HSP90 ( 13 , 30 ). It has been reported that inhibition of HSP70 expression may lead to dysfunction of immune cells and reduce resistance to infectious infection during severe sepsis.…”
Section: Discussionmentioning
confidence: 99%